Study of PID Controller Mode at Biodiesel Pilot Plant at UTHM - Cheah, Choon Fong; Abu Bakar, Bachik (Progress in Engineering Application and Technology, 2023)
Due to the loss of resources, the next generation of students will face difficulty to understand the tuning process and Proportional Integral Derivative (PID) controller at Biodiesel Pilot Plant at UTHM. To manipulate and study processes, a variety of process controllers are used, but the PID controller is the simplest and often the most effective. The PID controller calculates the difference between the setpoint and the actual value and attempts to minimize it by adjusting the control input to achieve the desired output value. A PID controller regulates a process by utilizing three parameters: proportional (P), integral (I), and derivative (D). These parameters can be tuned to adjust their effect on the process. In order to determine the PID control parameters, the trial-and-error method involves observing the system’s response curve through closed-loop operation and then testing the parameters repeatedly based on the three criteria for excellent control quality, which are stability, minimum deviation, and minimum duration. According to the current simulation results, the appropriate parameters for PID in the heating process for VE201 were a proportional term with 2.0, integral with 20000ms, and derivatives 2500ms, while the appropriate parameters for PID in the heating process for VE202 were P = 1.0, I = 20000ms, D = 5000ms, considering the combination of stability, overshoot, and settling time. Finally, it is a fact that achieving all of the process control objectives with PID tuning is impossible. In terms of efficiency, choosing the relative importance of these objectives and then focusing on achieving the most important at the expense of the least important should be considered.